Implementasi Kurikulum 2013 di Madrasah Ibtidaiyah Kabupaten Semarang - A Masruhin (STAI Bumi Silampari, 2020)
This study aims to determine the implementation of the 2013 curriculum in Madrasah Ibtidaiyah, Semarang Regency and inhibiting and supporting factors. In this study using a qualitative research approach. The results of this study indicate that: first, in the implementation of the 2013 curriculum at the Madrasah Ibtidaiyah Tarbiyatul Aulad Jombor, it was carried out with active learning, creative, and using integrative thematic, scientific approaches, and auntent assessment. Secondly, the implementation of the 2013 curriculum at the Madrasah Ibtidaiyah Ma'arif Rowosari began in the 2017-2018 school year with first trials in grades one and four, which then in 2018-2019 were conducted in grades two and five. Whereas the third and sixth grades will only be held in 2019. Third, supporting factors include the manual given during the 2013 curriculum socialization, directions from supervisors, madrasa facilities, and outreach. The obstacles faced by the students are that they cannot read, distinguish letters and numbers for first grade, too much material and must be resolved with the target of one theme for more than one month, too many administrations to be resolved